The Optimal Analgesic Block for Total Knee Arthroplasty. Issue 3 (June 2017) - Bendtsen, T. F.; Moriggl, B.; Chan, V.; Børglum, J.
Abstract : (Abstracted from Reg Anesth Pain Med, 41:711–719, 2016) This article discusses the ideal analgesic block for total knee arthroplasty (TKA). The optimal peripheral nerve block technique can be identified with the use of surgical dissection techniques, examining the distribution of nociceptive generators, sensory innervation of the knee, and nerve topography in the thigh.